THE USE OF COLOR IN ADVERTISING: PSYCHOLOGICAL ASPECTS OF INFLUENCE ON CONSUMERS - ZHYGALO, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Studying the psychological aspects of the influence of color on consumers is extremely important in the field of marketing, advertising, design and many other fields. Colors can evoke different emotions, associations and reactions in consumers, and knowing these psychological influences allows you to create more effective and successful strategies to attract customers’ attention. The research focuses on studying the psychological aspects of the influence of color in advertising on consumers in order to determine the optimal strategies for using colors to increase the advertising campaigns effectiveness and achieve the desired response of consumers. The important role of visual perception in business and its impact on potential buyers is considered. The visual perception of a product is one of the strongest and most influential feelings for consumers. Visual elements such as branding, logos, packaging design, promotional materials, web design, video advertising and point of sale are used by producers and marketers to achieve various business goals. Psychological aspects of color perception, their influence on emotions and associations, and practical aspects of use in an advertising context are analyzed. It has been found that each color carries a unique emotional meaning, and the right choice of colors helps to create a positive perception of the advertising message. Aspects of attracting attention and interest of consumers, forming associations and product attributes with the help of color, as well as the influence of color on brand recognition are also considered. The importance of taking into account individual, cultural and contextual differences in color perception is emphasized. Choosing the wrong color combinations can negatively affect the perception of an advertising message. The context in which colors are used can also change their perception and effectiveness, as colors can have different associations in different cultures. Research has shown that color schemes can influence consumers’ purchasing decisions, so getting the color right can be strategically important to advertising success. Research is essential to the development of the psychology of marketing and advertising, allowing to attract and maintain a positive brand image, satisfy the needs of consumers and achieve success in the market.